A comparison of friction modifier performance using two laboratory test scales. (February 2019) - Buckley-Johnstone, L; Harmon, M; Lewis, R; Hardwick, C; Stock, R
This paper describes two methods, carried out at two different test scales, for assessing the friction modifier performance. Study A used the wear data from a full-scale rig test at the voestalpine Schienen GmbH and compared it with the wear data from twin disc tests using the SUROS test machine at the University of Sheffield. Study B compared the 'retentivity' data, from a full-scale rig at the University of Sheffield, with the data from the SUROS tests. Study A concluded that a good correlation existed between the two scales although assumptions made in the full-scale contact calculation introduce a large spread into the results. There was a greater correlation between the two data sets at more severe contact conditions. Study B showed a different baseline coefficient of traction between the two scales and that a longer test length is required to fully evaluate the 'retention' of the friction modifier on the full-scale rig. The paper expands on a previous conference presentation on the same subject. Additional information on the test procedure and test rigs is included here. Surface and subsurface analyses of the SUROS test samples have also been added. The analyses have shown that applying the friction modifier leads to a similar wear mechanism as for the dry contact, but the wear is less severe and there is less subsurface deformation. A discussion describing the differences in test scales and comparing lab tests to field operation is also included.